2012
DOI: 10.1155/2012/819497
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Based Predictive Geographical Routing for Inter-Vehicle Communication in Urban Areas

Abstract: Vehicular ad-hoc networks (VANETs) are highly mobile wireless ad hoc networks for vehicular safety and other commercial applications, whereby vehicles move non-randomly along roads while exchanging information with other vehicles and roadside infrastructures. Inter-vehicle communication (IVC) is achieved wirelessly using multihop communication, without access to fixed infrastructure. Rapid movement and frequent topology changes cause repeated link breakages, increasing the packet loss rate. Geographical routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The coded packet comprised of the two packets is represented by packet (3). By XORing either of packets (1) or (2) with the coded packet (3) will decode the coded packet and deliver the other packet as illustrated in (4) and (5). The pipe line encoding aims to reduce the coding delay as well as to further improve the throughput [3].…”
Section: Figure2 Mincut Max-flow Theoremmentioning
confidence: 99%
“…The coded packet comprised of the two packets is represented by packet (3). By XORing either of packets (1) or (2) with the coded packet (3) will decode the coded packet and deliver the other packet as illustrated in (4) and (5). The pipe line encoding aims to reduce the coding delay as well as to further improve the throughput [3].…”
Section: Figure2 Mincut Max-flow Theoremmentioning
confidence: 99%
“…Their proposed protocol achieves higher packet delivery ratio for the network, lower end-to-end delay, while keeping the energy consumption at the same low levels of GPSR. Furthermore, a grid-based predictive geographical routing protocol (GPGR) has been proposed by the researchers of [33]. Indeed, they used a map data to generate the road grid and to predict the moving position during the relay node selection process.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, it was noticed that the GPGR protocol reduces the possibility of link breakage and avoids falling on local maximum situation in urban scenarios. Moreover, authors of [33] suggested a new concept based on vehicles movement prediction. In fact, they estimated the Link Stability (LS) for each neighboring vehicle before selecting the next hop for data forwarding/sending.…”
Section: Related Workmentioning
confidence: 99%
“…In those classes, the header of the cluster will always be responsible for all the rebroadcasting operations. The methods that have been used in [23][24][25][26] are examples of such behavior.…”
Section: Mobile Relay Scenariomentioning
confidence: 99%